Optimasi nilai keausan pahat dan kekasaran permukaan benda kerja terhadap parameter pemesinan milling dengan benda kerja magnesium menggunakan kombinasi metode taguchi dan grey relational analysis - Dwiastanto, Lucius Patria Giri; Burhanuddin, Yanuar; Ibrahim, Gusri Akhyar (Universitas Muhammadiyah Metro, 2020)
The Taguchi method is widely used to determine the optimal quality of a process with a single response. While for multi-response cases, Grey Relational Analysis (GRA) and Principal Component Analysis (PCA) are widely used. With multi-phone GRA, it can be simplified into one single response. Tool wear and surface roughness of the workpiece in the milling machining process is affected by the diameter of the tool, depth of feed, spindle speed, and feeding speed. This study examines the response of tool wear and work surface roughness with three levels and four factors. For tool diameters, using 6.8 mm and 10 mm. The depth of feed used 1; 1,5 mm and 2 mm. Spindle speeds at 910, 1280, and 1700 rpm. While the feeding speed is 75 mm/minute, 145 mm/minute, and 220 mm/minute. Optimal results obtained in conditions of 6 mm tool diameter with 1,5 mm depth of feeding, spindle speed of 1280 rpm, and feeding speed of 75 mm/minute. The optimal response obtained is 0,059 mm for tool wear and 0,364 μm for work surface roughness. The significant factor influencing is the feeding speed which influences 76,14 %.Keywords: Grey Relational Analysis, Principal Component Analysis, Taguchi Method, Milling, Tool Wear, Roughness